TV News Channels in Peru. Analyzing Information and Investigation - Macalupú Cumpén, Pablo (2016)
TV News Channels in Peru exists since late nineties. This kind of media appeared as a public necessity because, in that moment, news coverage was coming from TV stations that negotiated its editorial terms with Fujimori and Montesinos. The second TV News Channel in Peru was Canal N (the first -Cable Canal de Noticias- also had negotiated with https Montesinos). This TV station was founded in 1999 and was the only one that presented balanced and impartial approaches to their audience in that time on TV. Since 2010, other channels have emerged, such as Willax TV, ATV+ Noticias, RPP TV and TV Perú 7.3. Recently, Capital TV and Exitosa appeared as an alternative space to present their radio news programmes but in an audiovisual format. Therefore this editorial diversity invites us to analyse in detail their approaches and contents. In this article, we will review the coverage of Rodolfo Orellana capture and the report about Óscar López Meneses’ irregular police safeguard, a man linked to Vladimiro Montesinos.